Protective effect of potassium application on NaCl induced stress in tomato (Lycopersicon esculentum L.) genotypes. (8th August 2020) - Jan, Muhammad; Anwar ul Haq, Muhammad; ul Haq, Tanveer; Ali, Anser; Hussain, Safdar; Ibrahim, Muhammad
Abstract: Salinity is a major limiting factor which disrupts the plant physiology as well as reduces the plant growth. Salinity stress can be minimized by potassium application as it regulates the plant growth. Protective effect of potassium application on NaCl induced stress in two tomato genotypes (Nasir and Skyland-II) at two levels of NaCl (0 and 7.5 dS m −1 ) combined with two levels of soil -applied K (0 and 4.50 mM) as well as with two levels of foliar-applied K (0 and 2% solution) was studied. Results showed that Skyland-II had significantly more dry biomass production, shoot K + concentration under saline condition (7.5 dS m −1 ) and Nasir tomato genotype. Potassium contents were significantly higher when potassium was applied which reduced the adverse effect of salinity and thus enhanced the plant biomass. The increasing concentration of potassium in the Skyland-II genotype positively affected chlorophyll contents, stomatal conductance and K + /Na + ratio. Salinity stress adversely reduced plant growth in both of the genotypes. It was concluded that potassium application improved plant growth especially in the Skyland-II genotype. Comparing the application methods, the soil applied potassium improved plant growth and decreased the adverse effect of salinity and could be used as an effective method for better production.